Human resources development in farming and fisheries for food security - Abdulla Nadhiya; Vasylieva Natalia (E3S Web of Conferences)
The article delves into the issues of providing food security in the Maldives, a nation that regularly faces adverse weather conditions and natural disasters. These challenges include tsunamis, heavy rainfall, and strong winds that damage infrastructure, fishing vessels, agricultural land, contaminate freshwater resources and wash away entire islands during the monsoon season. The research purpose was to support workforce development to compensate for shortage of natural and technical resources in farming and fisheries. The explored data was collected from Maldives Bureau of Statistics. The applied statistical and clustering methods proved that training in farming should share knowledge of cutting-edge technologies like Hydroponics and Pest control, benefit female farmers, involve the youth in local agriculture and be evenly distributed among the Atolls. The study findings based on ranking and trend analysis argue that unstable employment is the paramount problem in fisheries. It is recommended to optimize a number of fishermen per vessel by Atolls and promote acquiring skills of advanced eco-friendly fishing. Overall research results created a reliable foundation for systematic development of qualified human resources in farming and fisheries that are crucial for strengthening food security in a risky environment.